2020
DOI: 10.7575/aiac.ijels.v.8n.3p.105
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Childhood Traumas, Emotional Self-Efficacy and Internal-External Locus of Control in Predicting Psychological Resilience

Abstract: Psychological resilience is a broad concept that can be evaluated in the context of past experiences, emotional experiences and control mechanisms shaped by internal or external factors. In this study, the role of childhood traumas, emotional self-efficacy and the internal-external locus of control were investigated in predicting psychological resilience. The study included a total of 291 participants (208 females and 83 males) with average age of 20.29 (SD = 2.59). Childhood Trauma Questionnaire, Emotional Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…For the absence of an effect of the Ukraine war -though generating intense compassion for war victims, strongly focused by media coverage- it could we proposed that this population stressor possesses no threat to one’s own security and the sense of control in everyday life, in terms of the proximity of the stressor. Moreover, research on the impact of an individual’s locus of control on stress demonstrates that compassion and the ability to grant support (internal locus of control) is associated with better stress-regulation abilities [ 59 – 61 ]. This is also supported by researcher that demonstrates differences in risk perception and the people’s actions in relation to the Covid-19 pandemic and climate change, which may apply to the war too [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the absence of an effect of the Ukraine war -though generating intense compassion for war victims, strongly focused by media coverage- it could we proposed that this population stressor possesses no threat to one’s own security and the sense of control in everyday life, in terms of the proximity of the stressor. Moreover, research on the impact of an individual’s locus of control on stress demonstrates that compassion and the ability to grant support (internal locus of control) is associated with better stress-regulation abilities [ 59 – 61 ]. This is also supported by researcher that demonstrates differences in risk perception and the people’s actions in relation to the Covid-19 pandemic and climate change, which may apply to the war too [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has revealed that persons with a strong internal locus of control possess the ability to deal with numerous extremely stressful life events [ 70 ]. An association between internal locus of control and resilience was already found [ 71 ]. However, it should be kept in mind that only a fraction of possible influencing factors conducive to coping with the experience of stressors were collected and analyzed in the current study.…”
Section: Discussionmentioning
confidence: 95%
“…For the absence of an effect of the Ukraine warthough generating intense compassion for war victims, strongly focused by media coverage-it could we proposed that this population stressor possesses no direct threat to one's own security and the sense of control in everyday life. Moreover, research on the impact of an individual's locus of control on stress demonstrates that compassion and the ability to grant support (internal locus of control) is associated with better stress-regulation abilities [47][48][49] . Thus, it could be speculated that Germans who feel distress related to the Ukraine crisis might buffer this risk by for example actively engaging into aid activities.…”
Section: Discussionmentioning
confidence: 99%